2016
DOI: 10.1080/00015458.2015.1128197
|View full text |Cite
|
Sign up to set email alerts
|

Early myotomy and fundoplication in achalasia in childhood: a single-centre experience for 22 years

Abstract: Introduction The aim of this study was to review a single institution's experience with surgical interventions in children with achalasia and to determine treatment strategies for this rare disorder. Patients and methods This study is a retrospective analysis of 22 cases of childhood achalasia from 1991 to 2013. The patients were evaluated in terms of age, symptoms, interventions, intraoperative complications, and recurrent dysphagia. Results There were 13 boys and nine girls (7 months to 17 years old). The cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…[ 1 ] As a result, many children miss an early diagnosis and are managed as other conditions. [ 2 3 ] Hence, a study was conducted to understand the various manifestation of achalasia cardia in children which would help us diagnose the disease early and treat it to reduce morbidity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[ 1 ] As a result, many children miss an early diagnosis and are managed as other conditions. [ 2 3 ] Hence, a study was conducted to understand the various manifestation of achalasia cardia in children which would help us diagnose the disease early and treat it to reduce morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] The mean age at surgery in our study was consistent with other pediatric studies such as Erginel et al , Lee et al , Hallal et al , Corda et al , Karnak et al , Singh et al , Smits et al , Zagory et al , and Saliakellis et al as they reported mean age at surgery of 3.34 years, 13 ± 6 years, 11 years, 12 years, 8.3 years, 3.25 ± 0.4 years, 11.4 ± 3.4 years, 11.6 ± 5 years, and 10 years, respectively. [ 2 7 14 15 16 17 18 19 20 ] There was no gender predilection in adult studies while the pediatric studies showed a male preponderance. [ 2 3 7 14 15 16 17 18 19 20 ] However, our study showed a female preponderance (9:3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations